2005
DOI: 10.1002/em.20169
|View full text |Cite
|
Sign up to set email alerts
|

3,4‐Epoxy‐1‐butene, a reactive metabolite of 1,3‐butadiene, induces somatic mutations in Xpc‐null mice

Abstract: Xpc-null (Xpc-/-) mice, deficient in the global genome repair subpathway of nucleotide excision repair (NER-GGR), were exposed by intraperitoneal (i.p.) injection to a 300 mg/kg mutagenic dose of 3,4-epoxy-1-butene (EB), to investigate NER's potential role in repairing butadiene (BD) epoxide DNA lesions. Mutagenic sensitivity was assessed using the Hprt assay. Xpc-/- mice were significantly more sensitive to EB exposure, exhibiting an average 2.8-fold increase in Hprt mutant frequency (MF) relative to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(12 reference statements)
0
6
1
Order By: Relevance
“…The targeted ortho ‐diquinone metabolite was formed in all likelihood through the dihydrodiol intermediate, which was also observed in this study as metabolite M4. It is hypothesized that M4 itself was formed through an epoxide intermediate, which incidentally was not observed in our study, perhaps due to its rapid conversion into M4 or its highly reactive nature, which is a well‐known phenomenon for epoxides . The epoxide intermediate is thus shown in a dotted box in Fig.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The targeted ortho ‐diquinone metabolite was formed in all likelihood through the dihydrodiol intermediate, which was also observed in this study as metabolite M4. It is hypothesized that M4 itself was formed through an epoxide intermediate, which incidentally was not observed in our study, perhaps due to its rapid conversion into M4 or its highly reactive nature, which is a well‐known phenomenon for epoxides . The epoxide intermediate is thus shown in a dotted box in Fig.…”
Section: Resultsmentioning
confidence: 64%
“…It is hypothesized that M4 itself was formed through an epoxide intermediate, [44] which incidentally was not observed in our study, perhaps due to its rapid conversion into M4 or its highly reactive nature, which is a well-known phenomenon for epoxides. [45] The epoxide intermediate is thus shown in a dotted box in Fig. 14. Also, no para-dihydrodiol was observed, so the formation of para-diquinone is shown direct from the drug in the figure.…”
Section: Pathway Of Generation Of the Identified Metabolitesmentioning
confidence: 99%
“…Interestingly, knockdown of XPC, but not of XPA, in HeLa cells leads to mild sensitivity to etoposide, a topoisomerase II inhibitor known to cause double-strand breaks (DSBs) [59]. Moreover, XPC is involved in repair of butadiene epoxide induced DNA lesions through an unidentified pathway [60]. Also implicating XPC in DSB repair is increased XPC transcription in response to ionizing radiation and to cyanotoxin cylindrospermopsin [61, 62].…”
Section: To Seek Out New Life and New Civilizations: Novel Roles Omentioning
confidence: 99%
“…XPC functioning has been implied in other DNA repair pathways like base excision repair and non-homologous end joining or might be involved in redox homeostasis (D'Errico et al,2006;Despras et al,2007;Liu et al,2010;Okamoto et al,2008;Rezvani et al,2010;Shimizu et al,2003;Uehara et al,2009). Chemical exposures to B[a]P (Wickliffe et al,2006), 3,4-epoxy-1-butene (EB) (Wickliffe et al,2006), DMBA (Wijnhoven et al,2001) and UV-B (Ikehata et al,2007) also showed significantly enhanced mutant frequencies compared to wild type mice in several tissues. Direct comparisons to Xpa mice in these studies have not been made, however when Xpa and Xpc mice were exposed to pro-oxidants (DEHP and paraquat) for 39 weeks, Xpc again exhibited a higher mutant frequency than Xpa.…”
Section: Xpe/ Ddb2mentioning
confidence: 99%